Engaging Learners in Native Language Lessons Through Educational Games - Matkarimova , Sayyora (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
Contemporary linguistic pedagogy demands advanced paradigms to counter cognitive fatigue inherent in traditional grammar instruction. This study analyzes the structural impact of targeted educational games on intrinsic motivation and morphosyntactic retention in native language lessons. Utilizing a 14-week quasi-experimental framework, an N=185 primary student cohort was evaluated. Implementing integrated gamified didactics, researchers measured acquisition variances using generalized linear mixed models. Results indicate gamified interventions produced a 34.2% (p < 0.01) absolute improvement in active lexical retrieval and a 29.5% increase in structural syntax comprehension. The data confirms that contextualized linguistic play fundamentally optimizes semantic processing. Consequently, deploying targeted gamification is empirically required to maximize developmental linguistic competencies.